2007
DOI: 10.1162/jiec.2007.1165
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Life‐Cycle Inventories via Reconciliation with the Laws of Thermodynamics

Abstract: Obtaining reliable results from life‐cycle assessment studies is often quite difficult because life‐cycle inventory (LCI) data are usually erroneous, incomplete, and even physically meaningless. The real data must satisfy the laws of thermodynamics, so the quality of LCI data may be enhanced by adjusting them to satisfy these laws. This is not a new idea, but a formal thermodynamically sound and statistically rigorous approach for accomplishing this task is not yet available. This article proposes such an appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Preliminary studies on process‐based LCI have demonstrated its potential usefulness for identifying missing flows as well as correcting measurement errors (Hau et al. ; Yi and Bakshi ; Tan et al. ; Ardente et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary studies on process‐based LCI have demonstrated its potential usefulness for identifying missing flows as well as correcting measurement errors (Hau et al. ; Yi and Bakshi ; Tan et al. ; Ardente et al.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies have been proposed to obtain high‐quality data or to assess the impact of uncertainty, such as incorporating emission generation mechanisms (von Bahr and Steen ), assigning data quality indicators (Weidema and Wesnæs ), reconciling data with conservation laws (Hau et al. ), and conducting sensitivity analysis and Monte Carlo simulation (Van den Berg et al. ; Björklund ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors demonstrate the method by applying it to the estimation of uncertainty in hypothetical systems created with virtual data. An important recent development in the treatment of parameter uncertainty is the approach of Hau and colleagues to apply mass balance and thermodynamic principles to check and rectify LCI data sets (Hau et al 2007).…”
Section: Review Of Previous Workmentioning
confidence: 99%
“…Mass balance applied to materials I-O of processes is the standard tool. More recently, Bakshi and colleagues have developed a promising approach to rectify/correct process data using both mass balance and thermodynamic laws (Hau et al 2007).…”
Section: Process and Product Data Qualitymentioning
confidence: 99%